Concept of efficiency in administration: From Curzon onward - Pachauri, S.K. (1997)
Tracing roots of concern for efficiency in Indian administration, the author starts off with contributions made by Lord Curzon 100 years ago and his successors under the British rule. He then highlights the features introduced in Indian administrative system to safeguard efficiency following independence. He follows up the discussion with contributions made by few individual scholars, findings of reform bodies like ARC and Sarkaria Commission. Among most significant recent developments in this area, he discusses 73rd Constitutional Amendment, pressure of liberalisation, adoption of concept of efficiency audit in U.K., recommendations of Fifth Pay Commission, availing of information technology benefits in government along with certain other proposed measures which may help promote the cause of efficiency. - Reproduced
Keywords: Public administration - India; Public administration